Efficient Big Data Storage in Cloud with Unique Authentication Approach for Privacy Access - Subbalakshmi, S.; Madhavi, K. (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The growth of in-network services in the IT sector has a significant impact on the storage as well as distribution of data in the cloud. The main problem is addressing customers' worries about data security and privacy because this new computing along with service technology requires users to entrust their critical data to the cloud service provider (CSP). Due to these security and privacy concerns, organizations are still hesitant to put their data on the cloud. Existing encryption techniques can safeguard data secrecy, but there are several downsides, including the risk of sensitive data leakage due to access patterns. The proposed approach combines the production of distinct keys with a security algorithm. The improved Elliptic curve with Diffie-Hellman (IECDH) security technique is used in this study, where unique encryption and decryption data are used. This technique effectively decreased the computing difficulty and encrypted the data. In an experimental examination, evaluation metrics such as computing overhead, decryption time, encryption time, as well as key generation time are used to determine how well the proposed IECDH performs.